suara pasif dan suara aktif: suara pasif - M.Yusri Ali Lubis; Reysha Miranti (Cendekia Madani Nusantara, 2024)
Background: Expert guidelines recommend using active over passive voice to improve clarity in Englishacademic writing. However, few systematic reviews synthesize research on reader outcomes from texts writtenin the passive versus active voice. This paper reviewed experimental studies comparing the effects of active andpassive voice on reader comprehension in English academic writing. Methods: Following PRISMA guidelines,database searches identified quantitative studies manipulating voice in academic texts and measuringdifferential impacts on reader understanding. 9 eligible studies were analyzed narratively. Results: Studiesconsistently demonstrated reduced readability, slower processing, and lower comprehension scores for passiveversus active voice texts across reader groups and disciplines.On coherence ratings, grammatical errors, and comprehension questions, passive voice performed significantlyworse.Conclusions: Strong evidence confirms active voice improves reader comprehension over passive in academicwriting. However, strategic passive usage may still benefit writing on a situational basis. More research isneeded on providing effective instruction to EFL students on selectively deploying active/passive principles.Originality: This systematic review is the first to synthesize major studies comparing active and passive voiceimpacts on reader outcomes in academic writing. The consistent experimental results provide an empirical basisfor style guidelines favoring active voice for clarity.